A Qualitative Inquiry into Institutional and Pedagogical Strategies for Integrating the Eight Dimensions of Graduate Profile through Visual Arts Learning in Indonesian Primary Schools - Nurul Kemala Dewi; I Ketut Widiada; Siti Istiningsih; Muhammad Erfan; Abdul Rasyid; M. Irji Irlian Sandi (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
Although character education policies in Indonesia have expanded considerably in recent years, relatively little is understood about how schools strategically embed the newly mandated eight graduate profile dimensions within subject-specific instruction, particularly visual arts education. This study analyzes the institutional and pedagogical strategies employed at the school and classroom levels to integrate these eight dimensions through visual arts learning at the primary school level. A qualitative method was adopted, with the research conducted at SDN 14 Cakranegara, involving the school principal, Grade IV and Grade V classroom teachers, and ten purposively selected students. Data were collected through participant observation and in-depth interviews, then analyzed using data reduction, thematic categorization, and interpretive analysis. The trustworthiness of the findings was ensured through triangulation and peer debriefing. Findings indicate that school-level strategies include aligning vision and mission, the cultivation of a character-affirming school culture, the implementation of artist-in-residence programs, organizing extracurricular activities, conducting routine evaluations, and documenting character traits. At the classroom level, teachers integrate the dimensions into lesson planning, implement PjBL, utilize digital media, and promote collaborative reflection. Students reported internalizing key values: faith, citizenship, critical thinking, creativity, collaboration, independence, health awareness, and communication. The study proposes an integrative conceptual framework linking institutional practices, pedagogical design, and students’ creative experiences.